Winter Cholecalciferol Supplementation at 51°N Has No Effect on Markers of Cardiometabolic Risk in Healthy Adolescents Aged 14–18 Years. Issue 8 (15th June 2018) - Smith, Taryn J; Tripkovic, Laura; Hauger, Hanne; Damsgaard, Camilla T; Mølgaard, Christian; Lanham-New, Susan A; Hart, Kathryn H
Abstract: Background: Epidemiologic studies have supported inverse associations between low serum 25-hydroxyvitamin D [25(OH)D] and cardiometabolic risk markers, but few randomized trials have investigated the effect of vitamin D supplementation on these markers in adolescents. Objective: The objective of this study was to investigate the effect of winter-time cholecalciferol (vitamin D3 ) supplementation on cardiometabolic risk markers in white, healthy 14- to 18-y-old adolescents in the UK (51°N) as part of the ODIN Project. Methods: In a dose-response trial, 110 adolescents (mean ± SD age: 15.9 ± 1.4 y; 43% male; 81% normal weight) were randomly assigned to receive 0, 10 or 20 μg/d vitamin D3 for 20 wk (October–March). Cardiometabolic risk markers including BMI-for-age z score (BMIz), waist circumference, systolic and diastolic blood pressure, fasting plasma triglycerides, cholesterol (total, HDL, LDL, and total:HDL), and glucose were measured at baseline and endpoint as secondary outcomes, together with serum 25(OH)D. Intervention effects were evaluated in linear regression models as between-group differences at endpoint, adjusted for the baseline value of the outcome variable and additionally for age, sex, Tanner stage, BMIz, and baseline serum 25(OH)D. Results: Mean ± SD baseline serum 25(OH)D was 49.1 ± 12.3 nmol/L and differed between groups at endpoint with concentrations of 30.7 ± 8.6, 56.6 ± 12.4, and 63.9 ± 10.6 nmol/L in the 0, 10, and 20 μg/d groups, respectively ( P  ≤ 0.001). Vitamin D3 supplementation had no effect on any of the cardiometabolic risk markers (all P  > 0.05), except for lower HDL (−0.12 mmol/L; 95% CI: −0.21, 0.04 mmol/L; P  = 0.003) and total cholesterol (−0.21 mmol/L; 95% CI: −0.42, 0.00 mmol/L; P  = 0.05) in the 20 μg/d than in the 10 μg/d group, which disappeared in the fully adjusted analysis ( P  = 0.27 and P  = 0.30, respectively). Conclusions: Supplementation with vitamin D3 at 10 and 20 μg/d, which increased serum 25(OH)D concentrations during the winter-time, had no effect on markers of cardiometabolic risk in healthy 14- to 18-y-old adolescents. This trial was registered at clinicaltrials.gov as NCT02150122.